(untitled) (Research, Society and Development, 2022)
The objective was to evaluate the morphology and forage yield of white oat cultivated under different doses and sources of phosphate fertilization. The experimental design used was completely randomized in a 4x2 factorial scheme, with five replications. The treatments were four doses of phosphorus: 0, 35, 70 and 140 kg ha-1 of P2O5, and two sources of phosphorus: simple superphosphate (18% of P2O5) and reactive natural phosphate (33% of P2O5). There was an effect (p<0.05) of phosphate fertilization on dry matter (DM) production, with the application of 140 kg ha-1 of P2O5 from the single superphosphate source, showing the highest forage yield. DM production as a function of phosphate fertilization by simple superphosphate was adjusted by regression analysis to the quadratic model (Y = 1.091 + 0.0055*X + 9.537e-0.5*X², p = 0.0253, R² = 0.99), suggesting that the more phosphorus available to the plant, the greater its DM accumulation rate. DM production as a function of phosphate fertilization with natural phosphate was adjusted to the linear model (Y = 0.00413*X + 1.107, p = 0.0127, R² = 0.97), suggesting a constant increase in DM production with an increase on the availability of P2O5 for white oat. Single superphosphate was the most efficient source of phosphorus, ensuring greater production of dry matter in oat plants. Regardless of the phosphorus source, the inflection point of forage production of white oat with up to 140 kg ha-1 of P2O5 was not reached.